Exploring teachers' experiences of educational technology: a critical study of tools and systems - Clapham, Andrew (2012)
In this project I explore two teachers’ experiences, as ‘key informants’, of educational technology in a UK inner-city comprehensive school. I examine the meditational role of technology in these teachers’ activities and suggest that such an examination can improve what we understand about educational technology at the school. I discuss how technology is socially shaped and therefore not neutral, and of technologically mediated change being ecological change (Postman, 1992). I examine discourses of ‘techno-romanticism’ which locate technology as a transformational panacea for educational challenges - discourses which seemingly ascribe technology its own agency. This thesis challenges such viewpoints, and the technological hegemony they support, by examining technology not as state-of-that-art but as the ‘state-of-the-actual’ (Selwyn, 2010a).